The Impact of National Professional Qualification for Educational Leaders Program (NPQEL 2.0) on School Leaders: Impak Program Kelayakan Profesional Pemimpin Pendidikan Kebangsaan (NPQEL 2.0) Terhadap Pemimpin Sekolah - Hussin, Ahamad Bin; Yaacob, Md. Rahaimi bin Haji; Si Harun, Mahazi bin; Jusoh, Ruzina binti; Md Yassin, Zarina binti binti; Zakaria, Ashfahani binti; Yusoff, Noraisah binti; Liew, Yon Foi; Ibrahim, Sham bin; Zulkernain, Faizatoen binti; Abdullah, Jamelaa Bibi binti; Subramaniam, Sathiyabama; et al. (Management Research Journal, 2021)
The professional development is crucial to produce high-performing school leaders in Malaysia. A total of 744 senior school leaders have participated in the National Professional Qualification for Educational Leaders in the first intake of 2018. This study was conducted to explore the impact of the training program on the participants and school leaders. Data were collected through questionnaires, interviews and document review. The NPQEL 2.0 has a positive impact on leaders and school such as in co-curriculum achievement, provision of school facilities, and networking. The findings of the study were used to review and improve the program.